PDTM-15. EMBRYONIC STEM CELL SIGNATURE DRIVES ATYPICAL TERATOID/RHABDOID TUMOR DEVELOPMENT IN HUMAN PLURIPOTENT STEM CELL-DERIVED TUMOR MODEL. (11th November 2019) - Arakawa, Yoshiki; Terada, Yukinori; Mineharu, Yohei; Miyamoto, Susumu; Yamada, Yasuhiro
Abstract: BACKGROUND: Atypical teratoid/rhabdoid tumor (AT/RT), which harbors SMARCB1 mutation and exhibits a characteristic histology of rhabdoid cells, has a poor prognosis because of the lack of effective treatment. METHODS: To investigate the pathogenesis of AT/RT, we establish human SMARCB1 -deficient pluripotent stem cells (hPSCs). RESULTS: Although neural progenitors have been suggested as being a cell-of-origin of AT/RT, SMARCB1 -deficient hPSC-derived neural progenitor-like cells (NPLCs) give rise to mostly medulloblastoma-like tumors when transplanted into the mouse brain. In contrast, transplantation of SMARCB1 -deficient hPSCs cause AT/RT-like tumor containing a large number of typical rhabdoid cells. hPSC-derived tumors exhibit activation of embryonic stem cell-like gene expression signature (ESC-like signature) compare with NPLC-derived tumors. Forced activation of ESC-like signature by expression of reprogramming factors confers rhabdoid histology in SMARCB1 -deficient NPLC-derived tumors. Activation of ESC-like signature is associated with poor survival. Consistently, the activation of ESC-like signature is found in clinical specimens of AT/RT. Finally, we perform CRISPR/Cas9 knockout screening to inhibit activation of ESC-like signature in AT/RT. Our effort identifies candidate genes including RAD2 1 that encodes a key component within the cohesin complex. Notably, chemical inhibition of HDAC8 that indirectly targets the function of cohesin with simultaneous inhibition of EZH2 efficiently suppresses the activation of ESC-like signature and inhibits the growth of AT/RT cells both in vitro and in vivo . CONCLUSION: SMARCB1 -deficient hPSCs offer the first human model for AT/RT, which uncovers the unappreciated role of the activated ESC-like signature in worse prognosis and unique histology. We propose that ESC-like signature could be a crucial therapeutic target for AT/RT.